2000
DOI: 10.7326/0003-4819-133-3-200008010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acidosis and Hepatic Steatosis Associated with Use of Stavudine: Report of Four Cases

Abstract: Because hepatic steatosis may be life-threatening, physicians should consider it as a possible cause of elevated hepatic aminotransferase levels among patients taking stavudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(97 citation statements)
references
References 19 publications
3
92
0
2
Order By: Relevance
“…Lactic acidosis is one of the most serious complications induced by prolonged therapy with NRTIs. When diagnosed, it often requires intensive care (32) and can be fatal in some patients (43). Therefore, lactic acid production is considered an important marker for characterization of NRTI-induced mitochondrial dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acidosis is one of the most serious complications induced by prolonged therapy with NRTIs. When diagnosed, it often requires intensive care (32) and can be fatal in some patients (43). Therefore, lactic acid production is considered an important marker for characterization of NRTI-induced mitochondrial dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that ddC can cause mitochondrial alterations in Schwann cells in a rabbit model of ddC-induced neuropathy (1). Didanosine (ddI) and stavudine (d4T) therapy can induce adverse effects such as hepatic steatosis and lactic acidosis, which are presumably also a consequence of drug-associated mitochondrial toxicity (5,32). In contrast, the etiology of abacavir-associated adverse effects such as hypersensitivity does not seem to involve mitochondrial toxicity (21,22).…”
mentioning
confidence: 99%
“…During the development of nucleoside analogues for FDA approval, it was determined that fialuridine, zidovudine, stavudine, and 2 0 ,3 0 -dideoxyinosine lead to hepatotoxicity. [47][48][49][50] Examination of liver biopsy specimens revealed microvascular steatosis signifying mitochondrial damage that was later confirmed in experimental models. 12 The FDA approves approximately 20 to 40 new drugs per year, and many-fold more start the approval process but fail during phase 1 to 3 clinical trials.…”
Section: Histologic Patterns Of Liver Injurymentioning
confidence: 99%
“…In vivo assessment of mitochondrial toxicity of metacavir in Rhesus monkeys after three months of intravenous administration 1667 www.chinaphar.com Zeng W et al Acta Pharmacologica Sinica npg zalcitabine (ddC), didanosine (ddI) and stavudine (d4T) [14][15][16] . A study of maternal-fetal exposure to AZT in patas monkeys also showed evidence for mitochondrial dysfunction including respiratory-chain defects and mtDNA reduction [17] .…”
Section: Introductionmentioning
confidence: 99%